Impacts of Small RNAs and Their Chaperones on Bacterial Pathogenicity - Djapgne, Louise; Oglesby, Amanda G. (Frontiers in Cellular and Infection Microbiology, 2021)
Bacterial small RNAs (sRNAs) are critical post-transcriptional regulators that exert broad effects on cell physiology. One class of sRNAs, referred to as trans-acting sRNAs, base-pairs with mRNAs to cause changes in their stability or translation. Another class of sRNAs sequesters RNA-binding proteins that in turn modulate mRNA expression. RNA chaperones play key roles in these regulatory events by promoting base-pairing of sRNAs to mRNAs, increasing the stability of sRNAs, inducing conformational changes on mRNA targets upon binding, or by titrating sRNAs away from their primary targets. In pathogenic bacteria, sRNAs and their chaperones exert broad impacts on both cell physiology and virulence, highlighting the central role of these systems in pathogenesis. This review provides an overview of the growing number and roles of these chaperone proteins in sRNA regulation, highlighting how these proteins contribute to bacterial pathogenesis.